2007
DOI: 10.1002/ejsp.420
|View full text |Cite
|
Sign up to set email alerts
|

Biassed processing of persuasive information: on the functional equivalence of cues and message arguments

Abstract: Research on persuasion has shown that inferences based on heuristic or peripheral cues can bias the subsequent processing of persuasive messages. Two studies (total N ¼ 296) examined the additional possibilities that a message argument can serve as a biassing factor and cue-related information can serve as the target of processing bias. It was demonstrated that a message argument can bias (a) the processing of subsequent other message arguments (Study 1) and (b) the processing of subsequent cue information (St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 27 publications
2
10
0
1
Order By: Relevance
“…Erb & Kruglanski, 2005;Erb et al, 2003), which suggests that when informational sets are short and, therefore, requiring less processing effort, the message argument will be sufficient to cause attitude change, all else being equal (e.g. communicator characteristics; Erb, Pierro, Mannetti, Spiegel, & Kruglanski, 2007;Kruglanski & Thompson, 1999). To our knowledge, this proposition has not been tested in relation to belief in CTs, although it is V. Swami et al consistent with the suggestion that informational framing will have an impact on such beliefs (Butler et al, 1995;Sunstein & Vermeule, 2009).…”
Section: Studymentioning
confidence: 99%
“…Erb & Kruglanski, 2005;Erb et al, 2003), which suggests that when informational sets are short and, therefore, requiring less processing effort, the message argument will be sufficient to cause attitude change, all else being equal (e.g. communicator characteristics; Erb, Pierro, Mannetti, Spiegel, & Kruglanski, 2007;Kruglanski & Thompson, 1999). To our knowledge, this proposition has not been tested in relation to belief in CTs, although it is V. Swami et al consistent with the suggestion that informational framing will have an impact on such beliefs (Butler et al, 1995;Sunstein & Vermeule, 2009).…”
Section: Studymentioning
confidence: 99%
“…Simply, the early information could make accessible certain conclusions serving as evidence for further inference rules in whose light the subsequent information might be interpreted (Higgins, Rholes, & Jones, 1977). We conducted two experiments to test this idea (Erb, Pierro, Mannetti, Spiegel, & Kruglanski, 2004). In the first, we looked at the biasing effects of early message arguments on processing subsequent message arguments and found that attitudes toward aspects highlighted in the subsequent arguments was biased by the quality of the initial message argument under high, but not low, processing motivation.…”
Section: Research In the Unimodel Paradigmmentioning
confidence: 99%
“…As reported in the literature on heuristic and systematic processing literature (e.g. Chen, Shechter, & Chaiken, 1996;Erb, Pierro, Mannetti, Spiegel, & Kruglanski, 2007;Livingston & Sinclair, 2008;Tetlock, 1983;Tetlock, Skitka, & Boettger, 1989), when individuals feel high levels of accountability, they feel a greater need to process their thoughts in great detail, possess higher sufficiency thresholds, and are more likely to deploy systematic processing. Thus, the accountability measure may reflect appraisals associated with Type 2 worry; the other VAS measures may better reflect Type 1 worry appraisals.…”
Section: Discussionmentioning
confidence: 89%